Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/1365-2656.13438
|View full text |Cite
|
Sign up to set email alerts
|

Maternal allocation in relation to weather, predation and social factors in a colonial cooperative bird

Abstract: Females may adjust prenatal allocation in relation to ecological conditions that affect reproductive success, such as weather conditions or predation risk. In cooperative breeders, helpers might also influence reproductive success, and previous studies suggest that females can lay smaller eggs or larger clutches when breeding with more helpers. Although recent work suggests that helper effects can vary according to climatic variables, how social and ecological factors interact to shape prenatal allocation is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 77 publications
(136 reference statements)
3
29
1
Order By: Relevance
“…Most colonies in the study area have been captured since 1993 and birds were marked with numbered metal rings and unique colour combinations (Fortuna et al 2021 ). The data set used here includes the breeding seasons of 2011/2012 and from 2013/2014 to 2018/2019.…”
Section: Data Collectionmentioning
confidence: 99%
“…Most colonies in the study area have been captured since 1993 and birds were marked with numbered metal rings and unique colour combinations (Fortuna et al 2021 ). The data set used here includes the breeding seasons of 2011/2012 and from 2013/2014 to 2018/2019.…”
Section: Data Collectionmentioning
confidence: 99%
“…The direction and magnitude of the response are expected to be inluenced by the species' life-history strategy and especially by the efects of maternal investment on mother's survival prospects and chances of breeding successfully in the future (Russell and Lummaa 2009). In birds, cooperatively breeding species tend to be long-lived (Arnold and Owens 1998;Downing et al 2015), and for long-lived species, maximization of lifetime reproductive success was suggested to be more eiciently achieved through increasing the number of breeding events in life than through increased investment in each breeding event (Ghalambor and Martin 2001;Drent and Daan 2002;Reid et al 2003), In agreement, a recent meta-analysis on 10 cooperatively breeding birds highlighted a tendency for mothers to reduce egg size in larger groups in most species studied (Dixit et al 2017; but see Fortuna et al 2021).…”
Section: Introductionmentioning
confidence: 88%
“…These weavers are facultative cooperative breeders, with up to eight helpers assisting a breeding pair in raising the chicks, notably by feeding them (Covas et al 2008). This lighter parental workload may increase the survival of young female breeders (Paquet et al 2015b) but has no detectable association with clutch size (Covas et al 2008;Fortuna et al 2021). Helpers are most often the ofspring of one or both breeders (Covas et al 2006).…”
Section: Species and Study Areamentioning
confidence: 99%
“…1101/2021.11.11.468195 doi: bioRxiv preprint fish). Three studies of cooperative birds have reported no evident relationship between egg size and the availability of help (Koenig et al 2009;Lejeune et al 2016;Fortuna et al 2021), and just one study has reported the reverse relationship. Iberian magpie (Cyanopica cooki) mothers with more helpers lay larger eggs and feed their nestlings at higher rates, consistent with the predictions of the differential allocation hypothesis (Valencia et al 2006(Valencia et al , 2017Savage et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of cooperative birds have now reported that, after controlling for variation in clutch size, mothers with (more) helpers lay smaller eggs; the pattern predicted by the load-lightening hypothesis (e.g., Malurus cyaneus (Russell et al 2007); Corvus corone corone (Canestrari et al 2011); Vanellus chilensis (Santos & Macedo 2011); Philetairus socius (Paquet et al 2013); see also Taborsky et al (2007) for an experimental demonstration in fish). Three studies of cooperative birds have reported no evident relationship between egg size and the availability of help (Koenig et al 2009;Lejeune et al 2016;Fortuna et al 2021), and just one study has reported the reverse relationship. Iberian magpie (Cyanopica cooki) mothers with more helpers lay larger eggs and feed their nestlings at higher rates, consistent with the predictions of the differential allocation hypothesis (Valencia et al 2006(Valencia et al , 2017Savage et al 2015).…”
Section: Introductionmentioning
confidence: 99%